Pencegahan Stunting Menuju Generasi Sehat Kelurahan Belian - Juliana, Tinta; Jihan Febiyanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
Stunting is a condition in which children experience failure in growth (body and brain) as a result of prolonged and prolonged malnutrition. Caused by low nutritional intake such as vitamins, minerals and animal protein sources. In accordance with the national target in the National Strategy (Stranas) for Accelerating Stunting Reduction, the Riau Islands Province is targeting a reduction in stunting prevalence of 14% in 2024. Therefore, the aim of this community service is to prevent and reduce stunting rates in Batam City. This community service involves several partners, including the Botania Community Health Center, Awal Bros Hospital, Batam City Health Service, BKKBN, and the role of Awal Bos University students. The method used in this activity is to provide education about stunting, carry out pre-tests and post-tests, apart from that, there is also a demonstration on cooking a healthy menu. The results after providing education about stunting to parents of babies and toddlers at Posyandu Sehati, there was an increase in knowledge by 17%.